1979
DOI: 10.1152/jn.1979.42.6.1495
|View full text |Cite
|
Sign up to set email alerts
|

Luxotonic responses of units in macaque striate cortex

Abstract: 1. Single units in striate cortex were studied in alert macaques while they viewed a ganzfeld. Of the 385 well-isolated units studied for 10 min to 2 h, 24% gave "luxotonic" responses, i.e., their rate of discharge for 1 min or more in diffuse, featureless, wideangle illumination (20-450 cd/m2) was at least double that during a comparable period in darkness, or vice versa, and not attributable to eye movements of blinking. Those discharging faster in the light, "photergic" units, outnumber those responding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
60
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 38 publications
8
60
0
Order By: Relevance
“…Such a finding places important constraints on possible physiological mechanisms for signaling the brightness of uniform surfaces. In monkey, the majority of neurons signaling surface luminance respond with either an increase or a decrease in firing to changes in luminance (photergic or scotergic, respectively) (6,7). The responses in human visual cortex we observed may therefore reflect the activation of two neuronal subpopulations homologous to those observed in monkey, signaling dark and light, respectively.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Such a finding places important constraints on possible physiological mechanisms for signaling the brightness of uniform surfaces. In monkey, the majority of neurons signaling surface luminance respond with either an increase or a decrease in firing to changes in luminance (photergic or scotergic, respectively) (6,7). The responses in human visual cortex we observed may therefore reflect the activation of two neuronal subpopulations homologous to those observed in monkey, signaling dark and light, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…Theoretical accounts of surface perception have therefore often postulated a processing of ''filling in'' that mediates creation of surface representations at some level in the visual system (4,5). However, more recent reports suggest that some cells in primary visual cortex do indeed respond to the luminance of uniform surfaces (6)(7)(8)(9)(10). Furthermore, in humans there is a close relationship between perceived brightness contrast and responses in primary visual cortex (11)(12)(13)(14)(15), suggesting that other sensations of brightness may also be encoded in primary visual cortex.…”
mentioning
confidence: 99%
“…How the brain encodes such local and global brightness cues is unknown. Only a few studies have examined neuronal response to uniform surfaces (4)(5)(6)(7)(8)(9). These studies have shown that although cells modulated by luminance change are found as early as the retina and lateral geniculate nucleus (LGN), those modulated by perceived brightness change, which occur independent of actual luminance change over the receptive field (RF), can be found as early as the primary visual cortex (V1).…”
mentioning
confidence: 99%
“…We found that the MEG response was better accounted for by log-scaled luminance (Table 1, middle) than was the physical luminance of the stimulus (Table 1, left). Some electrophysiological studies with non-human primates reported that the electrical activity of neurons in the primary visual cortex depends linearly on the logarithm of luminance (Kayama et al, 1979;Kinoshita & Komatsu, 2001). There are also a few fMRI and EEG studies of humans, which suggest that the activation intensity in the primary visual cortex is linearly dependent on the logarithm of luminance contrast (Avidan, Harel, Hendler, Ben-Bashat, Zohary, & Malach, 2002;Boynton, Demb, Glover, & Heeger, 1999;Goodyear & Menon, 1998;Souza, Gomes, Saito, Filho, & Silveira, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A few electrophysiological studies with non-human primates have reported that individual Correspondence concerning this article should be addressed to Aki Kondo, Research Center for Advanced Science and Technology, The University of Tokyo, 4-6-1, Komaba, Meguro-ku, Tokyo, 1538904, Japan, (email: kondo@fennel.rcast.u-tokyo.ac.jp). neurons exhibit a compressive dependency of discharge rate on luminance, and that neural activity depends linearly on the logarithm of luminance in the primary visual cortex (Kayama, Riso, Bartlett, & Doty, 1979;Kinoshita & Komatsu, 2001).…”
mentioning
confidence: 99%